PARALLEL ALGORITMLARDA MA’LUMOTLARNI QAYTA IShLASh SAMARADORLIGI - Madaminov, U.A. (SCIENCE and SOCIETY, 2025)
This article lists methods for using the Open MP and Open CV compilers described in the process. The performance results of the Open MP and Open CV compilers are clearly shown in diagram form.
Keywords: OpenMP; OpenCV; productivity; algorithm; parallel; core; processor